Let f(x) = 3x + 1 and g(x) = 2 - x. Determine the values for a such that

A) (a)
B) f(a^2) = g(2a)

4 answers

Sub "a" in where x is...
A) 3a+1 = 2 -a and then solve for a
B) where ever you see an "x" in the first function set it to be a^2, then in g(x) where you see the x let it be (2a) and then solve for a
So you have 3a^2 + 1 = 2 - 2a move everything to the right hand side and factor : )
Thank you Ms Pi_3.14159265358979
You are very welcome! It is great to see diligent students working on math : )
pog